Description of three new species of the leafhopper genus Idioscopus Baker, (Hemiptera: Cicadellidae: Eurymelinae) from Yunnan, China - Wang, Xian-Yi; Wang, Jia-Jia; Zhou, Xiao-Ling; Dai, Ren-Huai (Zootaxa, 2021)
Three new species of the leafhopper genus Idioscopus Baker, 1915 from China: I. furcaprocessus sp. nov., I. longiprocessus sp. nov., and I. serratastylus sp. nov. are described and photographed based on specimens collected in Yunnan Province of southern China. These three new species can be recognised mainly by the coloration and male genitalia.